Water-walled microfluidics for high-optical finesse cavities - Shai Maayani (Nature Portfolio, 2016)
Micrometre-sized spheres of water can trap light, but they quickly evaporate and the light is lost. Here, the authors create water-droplet microcavities that can contain light for one million circulations by replenishing the evaporating fluid from a reservoir.